MORPHOLOGICAL CHANGES OF A LIVER BY HEPATITIS IN DOGS AND CATS - Локес, П. І.; Кравченко, С. О.; Локес-Крупка, Т. П.; Бурда, Т. Л. (Scientific Progress & Innovations, 2014)
Investigations found that by the development of hepatitis in dogs and domestic cats in liver an inflammatory process occurs in two forms - serous and hemorrhagic. Macroscopically, the liver is enlarged and swollen, its edges - blunted, capsule is strained, registered stagnation effects. Sectional picture erased. Changes in the vessels for both pathologies are similar. Inflammatory edema more expressed for serous form of hepatitis in cats. In both cases there is hypertrophy and hyperplasia of Kupffer cells and granular degeneration of hepatocytes.